ROLE OF PUBLIC PROCUREMENT IN INNOVATIVE ACTIVITY STIMULATION - Yuliya Tomilko (Krymskij Naučnyj Vestnik, 2015)
The article analyzes procurement regulating legal act in field of innovate product (works, services)public procurement and also practice of forming of demand on an innovation by participating of innovative enterprises in procurement procedure. Also, in article showed recommendation in innovation activities of Russian Federation improvement by means of public procurement.